Developing young learners' writing skills in informal situations using ICT facilities - Mat Daud, Nuraihan (2010)
Palletier (2008) states that technology plays a big role in developing children’s writing. She claims that the computer is one of the significant forms of technology because of its easy accessibility. Franco (2008) also stresses the importance of ICT in enhancing children’s writing development. He examines the use of different teaching methods in order to help young students improve their writing skills. This paper explores children use of ICT devices outside the classroom. It discusses the ICT facilities used by young learners to develop their writing skills. Each has its strength in developing these skills. Powerpoint and word processors are the two obvious tools that can be explored for this purpose. Strong parental support and guidance can help very young learners to develop their writing skills using these devices. A longitudinal study (four years) on one nine year old child shows that power-point alone provided an interesting tool for the child to develop various aspects of writing. The bigger children preferred sites which are more interactive. It was, however, found that the social networking sites did not necessarily improve their writing skills. The real audience, however, made these sites a suitable medium for developing their communication skills. Those who were serious about developing their writing skills often went for other facilities. This included the use of blogs. Others utilised other means such as disguising themselves as the speakers of the target language. All these reflect the potential these facilities have in producing independent learners particularly in developing writing skills.